Analisa Faktor-faktor yang Mempengaruhi Intention to Enroll (Niat untuk Mendaftar) Siswa Sekolah Menengah ke Perguruan Tinggi di Kota Batam - Listia Nurjanah; Jason Jason; Andina Fasha (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the factors influencing students' intentions to pursue higher education in Batam City. It found that prospective students are more likely to choose state universities (PTN) over private universities (PTS). This study used a quantitative approach, with a survey completed by 350 high school students. The analysis revealed that attitudes, social media, and advertising significantly influence students' intentions to pursue higher education in Batam City.